2010 4th International Conference on Bioinformatics and Biomedical Engineering 2010
DOI: 10.1109/icbbe.2010.5518078
|View full text |Cite
|
Sign up to set email alerts
|

The Cloning and Analysis of a Partial Lipase Gene Sequence of Staphylococcus hominis GIMT1.079: Partial Lipase Gene Sequencing of S. hominis

Abstract: Lipase activity is common in staphylococci. Based on the blast of various known staphylococcal lipase DNA sequences, the degenerate primers were derived to amplify a 782-bp consensus lipase gene sequence of Staphylococcus hominis GIMT1.079, which encoded a deduced polypeptide of 260 amino acid (aa) residues. The alignment of aa sequence revealed that this 260-aa partial lipase of S. hominis shared high homology with those conserved parts of other 11 deduced staphylococcal lipases, in the range of the lowest 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…All the DNA and amino acid sequences here were analyzed using DNAMAN software (Lynnon Corp., Canada). For the convenient alignment of the amino acid sequences, the abbreviations were applied for the consensus lipase stretches from the selected strains with GenBank accession numbers in the blankets behind: S. aureus NCTC 8325, SAL (NC_007795); S. capitis SK14, SCaL-1 (EEE49083); S. caprae TCCC 11546, SCpL (GU451683); S. carnosus TM300, SCnL (AM295250); S. epidermidis ATCC 12228, SEL-1 (NP_763800); S. epidermidis M23864:W1, SEL-2 (EES41415); S. haemolyticus L62, SHaL (AF096928); S. hominis GIMT1.079, SHoL (GU111713) [10]; S. hyicus, SHyL (X02844); S. saprophyticus 7108, SSL (AY551101); S. warneri, SWL (AF208033) and S. xylosus DSM 20266, SXL (AF208229).…”
Section: B Sequence Analysis Of S Caprae Partial Lipase Genementioning
confidence: 99%
See 1 more Smart Citation
“…All the DNA and amino acid sequences here were analyzed using DNAMAN software (Lynnon Corp., Canada). For the convenient alignment of the amino acid sequences, the abbreviations were applied for the consensus lipase stretches from the selected strains with GenBank accession numbers in the blankets behind: S. aureus NCTC 8325, SAL (NC_007795); S. capitis SK14, SCaL-1 (EEE49083); S. caprae TCCC 11546, SCpL (GU451683); S. carnosus TM300, SCnL (AM295250); S. epidermidis ATCC 12228, SEL-1 (NP_763800); S. epidermidis M23864:W1, SEL-2 (EES41415); S. haemolyticus L62, SHaL (AF096928); S. hominis GIMT1.079, SHoL (GU111713) [10]; S. hyicus, SHyL (X02844); S. saprophyticus 7108, SSL (AY551101); S. warneri, SWL (AF208033) and S. xylosus DSM 20266, SXL (AF208229).…”
Section: B Sequence Analysis Of S Caprae Partial Lipase Genementioning
confidence: 99%
“…Since the year 1985 when Goetz et al [4] reported the first nucleotide sequence of a Staphylococus hyicus (phospho)lipase, till now at least 16 distinct lipase genes from 12 different staphylococcal species have been published, the biochemical properties of some lipases were also investigated [5][6][7][8][9][10]. In general, all these deduced staphylococcal lipases are organized as pre-pro-proteins in cytoplasm, then secreted into the culture media in pro-lipase forms, and finally processed as mature forms by the host extracellular proteases.…”
Section: Introductionmentioning
confidence: 99%
“…The liberated free fatty acids function as nutrients for the persistence of colonized bacteria. The free fatty acids (the end products of lipolytic activity) are known to harm several immune system functions, thus might have an indirect influence on their pathogenic potential [4,15,36,37]. The most important aspect of the secreted lipases that took part in pathogenesis is the discovery of antilipase IgG antibodies in patients experiencing infections by S. aureus, enriching the virulent potential of extracellular lipases [38,39].…”
Section: Discussionmentioning
confidence: 99%